Gene expression analysis of Atlantic salmon gills reveals mucin 5 and interleukin 4/13 as key molecules during amoebic gill disease - Marcos-López, Mar; Calduch-Giner, Josep A.; Mirimin, Luca; MacCarthy, Eugene; Rodger, Hamish D.; O'Connor, Ian; Sitjà-Bobadilla, Ariadna; Pérez-Sánchez, Jaume; Piazzon de Haro, María Carla (Scientific Reports, 2018)
Amoebic gill disease (AGD) is one of the main diseases affecting Atlantic salmon (Salmo salar L.) mariculture. Hallmarks of AGD are hyperplasia of the lamellar epithelium and increased production of gill mucus. This study investigated the expression of genes involved in mucus secretion, cell cycle regulation, immunity and oxidative stress in gills using a targeted 21-gene PCR array. Gill samples were obtained from experimental and natural Neoparamoeba perurans infections, and sampling points included progressive infection stages and post-freshwater treatment. Up-regulation of genes related to mucin secretion and cell proliferation, and down-regulation of pro-inflammatory and pro-apoptotic genes were associated with AGD severity, while partial restoration of the gill homeostasis was detected post-treatment. Mucins and Th2 cytokines accoun ted for most of the variability observed between groups highlighting their key role in AGD. Two mucins (muc5, muc18) showed differential regulation upon disease. Substantial up-regulation of the secreted muc5 was detected in clinical AGD, and the membrane bound muc18 showed an opposite pattern. Th2 cytokines, il4/13a and il4/13b2, were significantly upregulated from 2 days post-infection onwards, and changes were lesion-specific. Despite the differences between experimental and natural infections, both yielded comparable results that underline the importance of the studied genes in the respiratory organs of fish, and during AGD progression. Irish Research Council (Employment Based Postgraduate Programme Project ID EBPPG/2013/2) European Commission under the TNA programme (project ID AE030036) within AQUAEXCEL2020 project (652831). CSIC PIE project no. 201740E013. Peer reviewed